Gamification as strategy for software process improvement: A systematic mapping [Gamificación como estrategia para la Mejora de procesos software: Un mapeo Sistemático] (2017)
Actually, software development companies face major challenges related to the implementation of high quality software products at even-increasing speed. In response of such challenges emerges software process improvement as a discipline oriented to continuous improvement of business process of such companies. However, the implementation of software process improvement approaches shows problems related to the human factor such as lack of motivation and commitment of the work teams. An alternative to address such problems is incorporating gamification in the imple mentation of software process improvement initiatives. In this article the authors describe a systematic mapping of the use of gamification in software process improvement approaches in order to identify and categorize existing proposals as well as future lines of work in this area. © 2017 AISTI.